Catenary action of RC beam-column joints in sub-assemblies - Lai, Weng Hong (2011)
In progressive collapse, the failure of a local structural component can eventually lead to the entire collapse of the whole building. In order to mitigate the impact, the structure will seek alternate load paths to maintain the stability and equilibrium of the whole structure. One example of such alternate load paths is catenary action. During this phase, tensile force in the beam is mobilised to resist the additional loads on the structure. This project aims to investigate the development of catenary action in reinforced concrete (RC) frame structures where a middle column is removed. Two specimens --F1-cd (ns) [conventional design of RC sub-assemblage with non-seismic detailing] and F2-cd(s) [conventional design of RC sub-assemblage with seismic detailing] were designed and tested to study the structural mechanisms of the full RC beam-column sub-assemblages when subjected to middle column removal scenario.